Steroid Signaling in Autophagy. - Bradic, I.; Rewitz, K. (Journal of Molecular Biology, 2025)
Autophagy is a conserved cellular process essential for homeostasis and development that plays a central role in the degradation and recycling of cellular components. Recent studies reveal bidirectional interactions between autophagy and steroid-hormone signaling. Steroids are signaling molecules synthesized from cholesterol that regulate key physiological and developmental processes - including autophagic activity. Conversely, other work demonstrates that autophagy regulates steroid production by controlling the availability of precursor sterol substrate. Insights from Drosophila and mammalian models provide compelling evidence for the conservation of these mechanisms across species. In this review we explore how steroid hormones modulate autophagy in diverse tissues and contexts, such as metabolism and disease, and discuss advances in our understanding of autophagy's regulatory role in steroid hormone production. We examine the implications of these interactions for health and disease and offer perspectives on the potential for harnessing this functionality for addressing cholesterol-related disorders.